The Effects of 0.01% Atropine on Adult Myopes’ Contrast Sensitivity - Cheng, Ziyun; Mei, Jianhui; Cao, Suqi; Zhang, Ran; Zhou, Jiawei; Wang, Yuwen (Frontiers in Neuroscience, 2021)
PURPOSE: Atropine at a low concentration is considered a safe and effective treatment to mitigate myopia progression. However, the application of administering atropine at a low dose on visual functions other than best corrected visual acuity has not been investigated. In this study, we investigate the short-term (12,16, 20 hours) and long-term (1,2,4 weeks) effects of 0.01% atropine (i.e., 0.1mg/ml) on contrast sensitivity in patients with myopia. METHODS: Thirty adults (23.33 ± 2.93 years old) with myopia between -1.00 and -6.00 diopters (D), astigmatism of -1.50 D or less, and anisometropia of 1.00 D or less, participated this prospective, masked, placebo-controlled, randomized study. The participants were randomly assigned to receive 0.01% atropine or polyvinyl alcohol eye drops once nightly to both eyes for four weeks. Contrast sensitivity was measured binocularly at baseline and 12, 16, 20 hours, 1, 2, and 4 weeks after the first use of the eye drops. RESULTS: There was no statistically significant differences of contrast sensitivity found between atropine and placebo-controlled groups in both short-term and long-term. There was no statistically significant interaction effect found between the time and group. CONCLUSIONS: We demonstrated no significant deleterious effect of 0.01% atropine on adult myopes’ contrast sensitivity.